Obsessive Compulsive Disorder Case Study from the Contingential Analysis Perspective - Rodríguez Campuzano, María Lourdes (Pensando Psicología, 2018)
Introduction: This paper presents a case study of a behavior diagnosed as obsessive-compulsive disorder. Method: The case is analyzed and treated by a method arising from the inter-behavioral approach called “contingency analysis.” The application of the method is illustrated by the analysis of two basic dimensions for this purpose: micro-contingency dimension and macro-contingency dimension. Some important aspects of the genesis of this behavior, as well as the analysis of the selected solutions, are described. The intervention objectives and the techniques used are also explained. Results: Because of the intervention, changes were obtained in the behavior of the user of the service (who was the mother of the person diagnosed with the disorder and her child so diagnosed). Conclusions: The article concludes by detailing the advantages of approaching a case study with the contingency analysis method.